A Decade of Horror: Understanding the Complexities of Conflict and Insecurity in North-central Nigeria through the Lens of Stakeholders - Oyebode, Musibau Olabamiji (Kashere Journal of Politics and International Relations, 2025)
The issue of violence and insecurity in north-central Nigeria have remained pervasive. This study examines the intricacies of conflict and insecurity in northcentral Nigeria. The study is pinned on grievance theory of social movement. The study adopts the survey method to obtain quantitative and qualitative data. A questionnaire was administered on 400 respondents and fourteen key informant interviews were conducted. Findings revealed that indigene/settler divide (x̄= 3.64), economic survival resulting in contestation for scarce resources (x̄=3.64), individual memories of community membership and identity (x̄= 4.17), manipulation of ethnic cleavages by political and economic elite (x̄= 4.21), multi-religious environment (x̄=3.67), inequitable distribution of state patrimony (x̄= 3.86), retaliatory spirit (x̄= 4.17) and criminality for pecuniary benefits (x̄= 4.00) are the causes of the crises. Farmers and herders (x̄= 3.81), terrorist-spillover (x̄= 3.41), unemployed youths (x̄= 2.83), conflict entrepreneurs (x̄= 4.26) and criminals (x̄= 4.21) are the perpetrators of violence in the area. Guerilla warfare (x̄=4.28), banditry (x̄= 4.21), cattle rustling (x̄= 4.15), reprisal attacks (x̄= 4.13) and arson (x̄= 4.16) are tactics used to perpetrate violence. Militarisation (x̄= 2.95), enactment of new laws (x̄= 2.85), setting up of commissions and panels of enquiries (x̄= 2.98) and prosecution of offenders (x̄= 2.85) have not been effective. Humanitarian interventions (x̄= 3.64), community vigilante groups (x̄= 3.64) and facilitated dialogues (x̄= 3.67) are working. While better policing is required, peacebuilding initiatives including non-kinetic methods like negotiation and provision of alternative economic valves are recommended to tackle divergent interests and address the underlying issues.